What's Going On? Reflections on Kratochwil's Concept of Law. (January 2016) - Werner, Wouter
This article focuses on two conceptual puzzles that arise out of Kratochwil's concept of law. The first is the dual meaning of the questions 'what is the law' and 'what is society'? I will argue that a sociological approach to these questions is unable to do justice to the specific position of the legal practitioner, for whom then these questions are first and foremost normative ones with possible far-reaching implications. The second is the relation between the validity and the binding force of law. In line with institutional approaches to law, I argue that legal language cannot be reduced to one form of linguistic practice, the production of binding decisions and norms of conduct. I will show how a broader conception of law as a form of linguistic activity opens up new research agendas in (international) law.